Overlapping approach Proton Pump Inhibitors/Nux vomica-Heel as new intervention for gastro-esophageal reflux management: Delphi consensus study - Battaglia, Edda; Bertolusso, Luciano; Del Prete, Marco; Monzani, Marco; Astegiano, Marco (World journal of gastroenterology : WJG, 2024)
BACKGROUND Gastro-esophageal reflux disease (GERD) may affect the upper digestive tract; up to 20% of population in Western nations are affected by GERD. Antacids, histamine H2-receptor antagonists, and Proton Pump Inhibitors (PPIs) are considered the referring medications for GERD. Nevertheless, PPIs must be managed carefully because their use, especially chronic, could be linked with some adverse effects. An effective and safe alternative pharmacological tool for GERD is needed. After the identification of potentially new medications to flank PPIs, it is mandatory to revise and improve good clinical practices even through a consensus process. AIM To optimize diagnosis and treatment guidelines for GERD through a consensus based on Delphi method. METHODS The availability of clinical studies describing the action of the multicomponent/multitarget medication Nux vomica-Heel, subject of the consensus, is the basic prerequisite for the consensus itself. A modified Delphi process was used to reach a consensus among a panel of Italian GERD specialists on the overlapping approach PPIs/Nux vomica-Heel as a new intervention model for the management of GERD. The Voting Consensus group was composed of 49 Italian Medical Doctors with different specializations: Gastroenterology, otolaryngology, geriatrics, and general medicine. A scientific committee analyzed the literature, determined areas that required investigation (in agreement with the multiple-choice questionnaire results), and identified two topics of interest: (1) GERD disease; and (2) GERD treatment. Statements for each of these topics were then formulated and validated. The Delphi process involved two rounds of questioning submitted to the panel experts using an online platform. RESULTS According to their routinary GERD practice and current clinical evidence, the panel members provided feedback to each questionnaire statement. The experts evaluated 15 statements and reached consensus on all 15. The statements regarding the GERD disease showed high levels of agreement, with consensus ranging from 70% to 92%. The statements regarding the GERD treatment also showed very high levels of agreement, with consensus ranging from 90% to 100%. This Delphi process was able to reach consensus among physicians in relevant aspects of GERD management, such as the adoption of a new approach to treat patients with GERD based on the overlapping between PPIs and Nux vomica-Heel. The consensus was unanimous among the physicians with different specializations, underlying the uniqueness of the agreement reached to identify in the overlapping approach between PPIs and Nux vomica-Heel a new intervention model for GERD management. The results support that an effective approach to deprescribe PPIs through a progressive decalage timetable (reducing PPIs administration to as-needed use), should be considered. CONCLUSION Nux vomica-Heel appears to be a valid opportunity for GERD treatment to favor the deprescription of PPIs and to maintain low disease activity together with the symptomatology remission.